CALCULATION OF INDUCTANCE OF THE INTERIOR PERMANENT MAGNET SYNCHRONOUS MOTOR - Phyong Le Ngo (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Interior permanent magnet synchronous motor (IPMSM) refers to salient-pole synchronous motors, characterized by inequality of inductances of longitudinal (d) and transverse (q) axes. Electromagnetic torque of IPMSM consists of two components: active torque and reactive torque; the latter depends on inductances of d and q axes. An analytical method to calculate own inductances and mutual inductances of a three-phase IPMSM is presented. Distributed windings of the stator are substituted by equivalent sine distributed windings. An interior permanent magnets rotor is substituted by an equivalent salient-pole rotor. Sections of a magnetic circuit comprising interior permanent magnets, air barriers and steel bridges are substituted by equivalent air-gap. The expressions of the magnetic induction created by current of the stator windings at each point of the air gap as well as of magnetic flux linkage of the stator windings have been obtained. The equations of the self-inductances of phases A, B, C, and of inductance of mutual induction are determined from magnetic flux linkage. The inductance of the d and q axes have been obtained as a result of transformation of the axes abc–dq. The results obtained with the use of the proposed analytical method and the finite element method are presented in the form of a graph; the calculations that have been obtained by these two methods were compared.